Studi Kelayakan Sistem PLTS Atap On-Grid 1000WP pada Pelanggan Listrik PLN 900VA R1M - Iswanjono Iswanjono; Tjendro Tjendro (LPPM Universitas Putera Batam, 2022)
To meet the 23% renewable energy mix target by 2025, the Indonesian government continues to encourage the installation of on-grid rooftop solar power generator systems for PLN electricity customers. However, the results were not as expected. This was due to the high investment costs and there were still many public doubts about the effectiveness of solar energy results in an effort to save PLN electricity bill payments. In this study, an on-grid rooftop solar power generator system with 1000WP solar panel power was implemented on the customer of electricity PLN 900VA R1M to determine the energy gain produced by the system in an effort to reduce the amount of PLN electricity bill payments. The results of the research for 6 months show that the daily average power of the solar system was 300 watts, with an average daily energy gain of 1.8kWH. The average daily electricity consumption of PLN is 7.85 kWH. The energy efficiency of the solar power generator system installed by PLN 900VA electricity customers can reach 23% with savings in billing costs for 6 months of 8%